Imaging and Applied Optics Technical Papers 2012
DOI: 10.1364/oft.2012.om2d.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ce3+ vs. Ce4+ during the Polishing of Silicon Dioxide and Silicon Nitride Films using Ceria Abrasives

Abstract: Removal rate mechanisms of silicon dioxide and silicon nitride films during chemical mechanical polishing using ceria particles-based dispersion in the presence and absence of different additives are discussed. Our results show that ceria particles give high silicon dioxide and silicon nitride removal rates due to the reactivity of the Ce 3+ species with silicon dioxide or the sub-oxide formed on the silicon nitride surface by hydrolysis. With several additives, complete blockage of the reactive species and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, significant work has focused on increasing the O vac concentration (i.e., Ce 3+ state) on the CeO 2 surface by incorporating various rate enhancing additives to increase oxide MRR. [12][13][14][15][16] Kim et al showed that the use of Ce 3+ enriched core-shell CeO 2 nanoparticles allowed for increased MRR in comparison to that of pristine CeO 2 . 12 Doi et al also showed an increase in MRR as a function of Ce 3+ concentration in which picolinic acid was used as a rate enhancer.…”
mentioning
confidence: 99%
“…Therefore, significant work has focused on increasing the O vac concentration (i.e., Ce 3+ state) on the CeO 2 surface by incorporating various rate enhancing additives to increase oxide MRR. [12][13][14][15][16] Kim et al showed that the use of Ce 3+ enriched core-shell CeO 2 nanoparticles allowed for increased MRR in comparison to that of pristine CeO 2 . 12 Doi et al also showed an increase in MRR as a function of Ce 3+ concentration in which picolinic acid was used as a rate enhancer.…”
mentioning
confidence: 99%